Performance, consumption and production: State governance and the uses and meanings of water in the Sardar Sarovar Project, Gujarat, India - Peter P. Mollinga; Pranjal Deekshit (University of Bonn, Center for Development Research (ZEF), 2025)
This paper analyses the performative, consumptive and productive uses and meanings of water in and of the Sardar Sarovar Project (SSP), a large dam with reservoir on the Narmada river, located at the border of Gujarat and Madhya Pradesh States, India. The main focus of the paper is how water is being used in the State of Gujarat, of which the SSP covers the larger part, and the meanings that water and the infrastructure that it supplies have acquired since water was released from the dam in the early 2000s. The water and the project were carriers of meaning well before the project got constructed and became operational - the project is best known for the opposition against its building. The paper looks at that history briefly also, to assess how meanings have changed, continued and been added to. While originally designed for agricultural use and hydropower generation, the scope of uses and meanings has considerably expanded in the past decades, and particularly since the dam has become operational. The use of the water of the Narmada river for domestic purposes and, through that, for urban and industrial development is now prominent. The paper reviews the relatively limited amount of scholarship on the functioning and imagining of the project since it became operational in 2002, theoretically explores how water infrastructure functions as 'logistical power' in state governance, and outlines an interdisciplinary perspective for further research.
Keywords: 330; Sardar Sarovar Project; water infrastructure; India; governance; power